Are Banks Really Special? New Evidence from the FDIC-Induced Failure of Healthy Banks - Ashcraft, Adam B (American Economic Review, 2005)
Recent bank failures are followed by significant and permanent negative declines in real county income. These declines are larger for small failures than for large failures per dollar of assets, are larger for bank failures than thrift failures, and are larger for bank closures than assisted mergers. More interestingly, the failure of even healthy banks has significant and permanent negative effects on economic activity.